Association of Urinary Sodium Excretion and Diabetic Kidney Disease in Patients With Type 2 Diabetes Mellitus: A Cross-Sectional Study - Huang, Yan; Liu, Wenhui; Liu, Jianfang; Guo, Dan; Zhang, Peizhen; Liu, Deying; Lin, Jiayang; Yang, Linjie; Zhang, Huijie; Xue, Yaoming (Frontiers in Endocrinology, 2021)
Background: Diabetic kidney disease (DKD) is the leading cause of end-stage kidney disease worldwide. Epidemiological evidence of the association between urinary sodium excretion and the presence of DKD in patients with type 2 diabetes mellitus (T2DM) has not yet been well established. Methods: We performed a cross-sectional study of 1545 patients with T2DM over aged 20 years old from January 2018 to December 2020. Urinary sodium excretion was measured by 24-hour urine samples in inpatients and morning fasting urine samples in outpatients. The associations between urinary sodium excretion and the risks of DKD were examined using stepwise regression analysis, logistic regression analysis and multivariable-adjusted restricted cubic splines (RCS). Results: Regression analysis showed that urinary sodium was independently associated with urinary albumin to creatinine ratio (UACR) level (P = 0.006) and the risks of DKD (P = 0.042). In multivariable-adjusted RCS analysis, urinary sodium excretion was significantly associated with UACR in all patients (P = 0.008), and exhibited a J-shaped relationship. Logistic regression analysis showed that increased urinary sodium excretion was significantly associated with increased risks of DKD [OR (95% CI); 1.56 (1.07-2.27); P = 0.020]. However, the relationships between urinary sodium excretion and the risks of DKD and albuminuria showed no significance, after further adjustment for HOMA-IR and ba-PWV (brachial-ankle pulse wave velocity) (Both P > 0.05). Conclusions: Higher urinary sodium excretion level was associated with increased risks of DKD among patients with T2DM, dependent of vascular sclerosis and insulin resistance.